Cytogenetic and molecular characterization of an atypical ETP-ALL case with BCL2 dependency: therapeutic implications for Venetoclax use - Francesco Gigliotti; Carolina Brescia; Salvatore Audia; Maria Eugenia Gallo Cantafio; Paola Malatesta; Michelle‑Li Bellisario; Roberta Torcasio; Renato Cantaffa; Eulalia Galea; Rodolfo Iuliano; Giuseppe Viglietto; Francesco Trapasso; et al. (Molecular Biology Reports, 2025)
Background Early T-cell precursor acute lymphoblastic leukemia (ETP-ALL) is a rare, high-risk subtype of T-ALL characterized by distinctive immunophenotypic and genomic features. It is often associated with induction failure and frequent relapses. Despite recent advances in its molecular characterization, the prognosis remains dismal, and effective targeted therapies are limited. Methods and results We report a pediatric, multi-refractory ETP-ALL case with novel cytogenetic alterations, including a 4q deletion and a t(16;18)(q24;q21) translocation. Molecular profiling revealed progressive activation of the BCL2 pathway and disruption of Th17-related immune markers. Ex vivo sensitivity assays performed at different disease stages demonstrated increasing BCL2 dependency. Based on these findings, venetoclax was administered on a compassionate-use basis, resulting in rapid hematologic recovery and a marked reduction in blast percentage. Conclusions This case highlights the role of clonal evolution and immune deregulation in accompanying BCL2 addiction in relapsed ETP-ALL. Altogether, our findings underscore the therapeutic potential of venetoclax in refractory pediatric ETP-ALL cases with progressive BCL2 dependency.